LANGUAGE INVESTIGATION ON IMPOLITENESS SERVED AT ‘INDONESIA LAWYERS CLUB’ TALK SHOW - Dita Sukmawati Putri; Dwi Purnanto; Miftah Nugroho (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
Impoliteness lately becomes a common habit occurring in people interaction. It is not only revealed at informal, but also formal circumstances. What are the forms and strategies of impoliteness appearing at formal conversations? This question is discussed through this research explanation. This paper is an attempt to investigate the impoliteness implementation uttered by speakers of the “Indonesia Lawyers Club” show—a popular program that presents a dialogue on issues of law and politic. As the consequence, the data sources were conversations uttered by ILC speakers involving impoliteness. This descriptive qualitative study applied the concept of Culpeper (1996) to gain deep comprehending on impoliteness in public usage. The result shows that there were four impoliteness strategies at the show, including bald on record impoliteness, positive impoliteness, negative impoliteness, as well as mock impoliteness.